Complex effects of helper relatedness on female extrapair reproduction in a cooperative breeder. (5th April 2021) - Hajduk, Gabriela K; Cockburn, Andrew; Osmond, Helen L; Kruuk, Loeske E B
Abstract: In cooperatively breeding species, the presence of male helpers in a group often reduces the breeding female's fidelity to her social partner, possibly because there is more than one potential sire in the group. Using a long-term study of cooperatively breeding superb fairy-wrens ( Malurus cyaneus ) and records of paternity in 1936 broods, we show that the effect of helpers on rates of extrapair paternity varied according to the helpers' relatedness to the breeding female. The presence of unrelated male helpers in a group increased average rates of extrapair paternity, from 57% for groups with no unrelated helpers, to 74% with one unrelated helper, to 86% with 2+ unrelated helpers. However, this increase was due in equal part to helpers within the group and males in other groups achieving increased paternity. In contrast, helpers who were sons of the breeding female did not gain paternity, nor did they affect the level of extra-group paternity (which occurred at rates of 60%, 58%, 61% in the presence of 0, 1, 2+ helper sons, respectively). There was no evidence of effects of helpers' relatedness to the female on nest productivity or nestling performance. Because the presence of helpers per se did not elevate extrapair reproduction rates, our results undermine the "constrained female hypothesis" explanation for an increase in extrapair paternity with helper number in cooperative breeders. However, they indicate that dominant males are disadvantaged by breeding in "cooperative" groups. The reasons why the presence of unrelated helpers, but not of helper-sons, results in higher rates of extra-group reproduction are not clear. Abstract : In superb fairy-wrens, unrelated helpers in a group increased extrapair paternity, both within and (unexpectedly) outside the group. The presence of helpers who were sons of the breeding female had no effect on mating patterns in this cooperatively breeding species. The results undermine a long-standing explanation for extrapair paternity, the "constrained female hypothesis, " which suggests that females assisted by helpers have more freedom to mate outside of their social partnership.